Modelo de propagação para redes sem fio fixas na banda de 5,8 GHZ em cidades típicas da região amazônica - CASTRO, Bruno Souza Lyra (Universidade Federal do Pará, 2012)
The study of propagation loss in the Amazon region cities involves an environment characterized by tropical climate and suburban environments densely arborous. Based in the importance of ISM band 5.8 GHz, this work presents a propagation model for this frequency band, combining the characteristics of attenuation experienced by a radio wave when it propagates in typical environments found in Amazon region cities. For such purpose, measurements of the received power were carried out in 335 fixed customers distributed in 12 towns in northern Brazil, which are served by digital inclusion program in the state of Pará, Navega Pará. Measurements with mobility were also carried out on the Federal University of Pará (UFPA) area. Still, it is presented the performance of the proposed model over other models (SUI model and COST231-Hata), described in the literature, when in fixed and mobile networks. Performance metrics such as RMS error and standard deviation were applied taking as reference the measured data. Tuning procedure of the model parameters is performed by the method of linear least squares, applied in two steps to reduce uncertainty about the parameters set. The proposed model achieved an RMS error of 3.8 dB and standard deviation of 2.3 dB, surpassing all other models that had RMS errors above 10 dB and standard deviations over 5 dB. The results show its efficiency on other models to predict losses in the range of 5.8 GHz in stationary and mobile systems.